2018
DOI: 10.1017/s0025315418000735
|View full text |Cite
|
Sign up to set email alerts
|

The influence of environmental conditions onParasagitta friderici(Chaetognatha) abundance in a subtropical estuary (south Brazil)

Abstract: Estuarine chaetognath population dynamics are poorly known worldwide. We have conducted eight seasonal campaigns (October 2007–August 2008) sampling three sectors in the subtropical Babitonga Bay estuary (26°S 48°W) in order to depict chaetognath abundance and population structure dynamics and test the influence of hydrography and food availability and type. Of three species sampled, Parasagitta friderici represented >93% of abundance in all samples and was examined in detail. There were no differences in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
(70 reference statements)
1
3
0
Order By: Relevance
“…Similarly, we observed the percentage of individuals with eggs present was moderately correlated with temperature (surface r = .455; bottom r = .460). This finding aligns with previous studies, which identified temperature as a significant driver in juvenile abundance(Nogueira Júnior et al, 2019), as well as egg development and laying times (reviewed inAlvariño, 1990), with laying occurring earlier in the day on warm days and most species breeding primarily in spring, although noting breeding does occur year-round in tropical waters.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…Similarly, we observed the percentage of individuals with eggs present was moderately correlated with temperature (surface r = .455; bottom r = .460). This finding aligns with previous studies, which identified temperature as a significant driver in juvenile abundance(Nogueira Júnior et al, 2019), as well as egg development and laying times (reviewed inAlvariño, 1990), with laying occurring earlier in the day on warm days and most species breeding primarily in spring, although noting breeding does occur year-round in tropical waters.…”
supporting
confidence: 92%
“…There were not enough individuals found in this study to make conclusions regarding S. bipunctata's reproductive seasonality. et al, 2019;Owre, 1960;Pierce, 1951;Pierce & Wass, 1962;Ulloa et al, 2000). While this study found weak correlations between salinity and chaetognath abundance, primarily oceanic species (such as F. enflata, S. bipunctata, and Sagitta megalopthalma) have demonstrated significant positive relationships between chaetognath assemblages and salinity levels (Gilmartin et al, 2020).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations